Prostate-Specific Membrane Antigen-Based Therapeutics - Naveed H. Akhtar; Orrin Pail; Ankeeta Saran; Lauren Tyrell; Scott T. Tagawa (Advances in Urology)
Prostate cancer (PC) is the most common noncutaneous malignancy affecting men in the US, leading to significant morbidity and mortality. While significant therapeutic advances have been made, available systemic therapeutic options are lacking. Prostate-specific membrane antigen (PSMA) is a highly-restricted prostate cell-surface antigen that may be targeted. While initial anti-PSMA monoclonal antibodies were suboptimal, the development of monoclonal antibodies such as J591 which are highly specific for the external domain of PSMA has allowed targeting of viable, intact prostate cancer cells. Radiolabeled J591 has demonstrated accurate and selective tumor targeting, safety, and efficacy. Ongoing studies using anti-PSMA radioimmunotherapy with 177Lu-J591 seek to improve the therapeutic profile, select optimal candidates with biomarkers, combine with chemotherapy, and prevent or delay the onset of metastatic disease for men with biochemical relapse. Anti-PSMA monoclonal antibody-drug conjugates have also been developed with completed and ongoing early-phase clinical trials. As PSMA is a selective antigen that is highly overexpressed in prostate cancer, anti-PSMA-based immunotherapy has also been studied and utilized in clinical trials.